A estrutura semântica interna de orações adverbiais temporais introduzidas por quando e realizadas pelo futuro do subjuntivo: uma abordagem funcionalista - Firmino, Lucas Henrique Xavier da Costa (2024)
The objective of this dissertation is to describe and analyze the syntactic, semantic and pragmatic aspects involved in the interpretation of the internal semantic structure of temporal adverbial clauses introduced by the conjunction when and carried out by the future subjunctive, in contemporary written Portuguese. This work found theoretical support in Discursive-Functional Grammar (2008), especially leading to the analysis of temporal adverbial clauses, here focused on the representational level of Discursive-Functional Grammar. Furthermore, other formal and functional criteria were taken into analysis, such as: the manifest temporal mode, the order of sentences, referential coherence, type of entity, temporal reference, factuality and presupposition. In this study, 1.003 (one thousand and three) data from the written language were considered, found in the Portuguese Corpus, which made it possible to carry out a synchronic and contemporary analysis of the object for this chosen work. I observed that the mode-temporal manifestation between the temporal clause and the nucleus is, predominantly, carried out by the future of the subjunctive (in the temporal) and present of the indicative (in the nucleus), other verbal modes and tenses are present in the nucleus clause, which creates a variability of temporal-mode combinations and readings (it is important to point out that the focus of this research is on the analysis of the temporal adverbial with future value); in addition to the verb ‘estar’ being the most productive in temporal prayer with future meaning. It was also found that they can appear as being of second order, with a dependent, non-factual and non-presupposed temporal reference; can appear as second-order, with independent temporal reference, being non-factual and non-presupposed and, finally, they can also appear as third-order, with independent temporal reference, being non-factual and not presupposed.